Component composition of the body in children with chronic kidney disease according to the results of bioimpedansometry - A. N. Zavyalova; D. A. Lebedev; V. P. Novikova; N. N. Smirnova; L. A. Firsova (Acta Biomedica Scientifica, 2023)
Body composition reflects the dynamic processes in a child’s development. The recommended restrictive diets for patients with advanced chronic kidney disease (CKD) contribute to a high risk of sarcopenic muscle wasting as diagnosed by bioimpedancemetry.The aim of the study. To assess BMI and body composition in children with CKD, to identify features of body composition in patients with different BMI Z-score values.Materials and methods. The physical development of 110 children with CKD of different stages was assessed. Patients were divided into two clusters: Group 1 (92 children) with BMI from 10.95 to 21.5 kg/m2, BMI Z-score did not exceed +2.0 (without obesity); Group 2 (18 children) – BMI from 24.11 to 37.2 kg/m2, Z-score BMI – more than +2.0 (obese). All underwent bioimpedancemetry, the proportion of fat and active cell mass was assessed. The comparison was carried out by nonparametric statistics methods.Results. Changes in body composition were revealed: children without obesity had severe protein-energy deficiency in 7 cases (7.6 %). The difference in the proportion of fat mass in children of different groups, Me [Q1; Q3]: Group 1 – 18.00 % [14.00; 22.00], Group 2 – 35.00 % [21.98; 41.00], (Mann – Whitney U-test: U = 279.5, p = 0.00001). In Group 1, the active cell mass was 53.50 % [51.00; 56.00], in Group 2 – 41.50 % [39.00; 47.00] (U = 174.5, p = 0.000001), there were no significant differences in other parameters of bioimpedancemetry.Conclusions. The proportion of active cell mass is lower in overweight children, with a significant predominance of the proportion of fat mass, which indicates the depletion of protein reserves due to their redistribution and possible insufficient alimentary intake in advanced stages of CKD.